A phase field approach to simulate intralaminar and translaminar fracture in long fiber composite materials. (15th July 2019) - Quintanas-Corominas, A.; Reinoso, J.; Casoni, E.; Turon, A.; Mayugo, J.A.
Abstract: The development of predictive numerical methods, which accurately represent the progressive failure of long fiber composite materials, is nowadays required for the achievement of optimized mechanical responses in terms of load bearing capacities of modern composite structures. In this investigation, two characteristic failure mechanisms of long fiber composites, denominated as intralaminar and translaminar fracture, are simulated by means of a novel version of the phase field (PF) approach of fracture. This numerical strategy encompasses a sort of gradient-enhanced damage formulation rooted in the Griffith theory of fracture, which is herewith extended for its use in composite laminates applications. In order to assess its verification and validation, the predictions obtained using the present formulation are compared against experimental results and two well-established alternative computational methods, which correspond to an anisotropic local-based continuum damage model and a cohesive zone model. The comparisons demonstrate that the PF approach with the proposed formulation provides reliable and robust predictions under quasi-static loading, but with a higher versatility regarding the potential of triggering arbitrarily complex crack paths with intricate topology over alternative techniques.